Thermal performance and surface analysis of steel-supported platinum nanoparticles designed for bio-oil catalytic upconversion during radio frequency-based inductive heating. (1st March 2019) - Bursavich, Jacob; Abu-Laban, Mohammad; Muley, Pranjali D.; Boldor, Dorin; Hayes, Daniel J.
Graphical abstract: Highlights: Pt-steel catalyst is designed for RF induction-based biofuel upconversion. High conductivity of steel balls resulted in rapid heating in induction reactor. High heating rates with temperatures of steel balls reaching 300 °C in under 20 s. Melting and degradation of the Pt nanoparticles with repeatedly heating at 525 °C. Abstract: A catalyst is designed for use in radio frequency (RF) induction-based biofuel upconversion. Stainless steel spheres are functionalized with Pt-nanoparticles through the use of a silane linker. These spheres are characterized via XRD, FTIR, SEM/EDX and XPS followed by generation of heating profiles in an RF induction heater. The high electric conductivity of the steel balls results in rapid heating which creates a positive temperature gradient across the surface with temperatures of the steel balls reaching 300 °C in under 20 s. Using a minimum of 3% power (150 W), temperatures over 525 °C are achieved within 150 s in a single steel ball experiment. A steel bed experiment is performed to simulate an induction-based catalytic upconversion of biomass pyrolysis vapors which indicates that temperatures over 195 °C are achieved in as little as 300 s using 5% power (250 W). Melting and degradation of the Pt nanoparticles is evident with repeated heating at temperatures of 525 °C and above, fortunately, typical catalysts designed for upconversion of pyrolysis oils are operating well below these temperatures. This form of heating has a potential to mitigate the effects of coke deposition on catalyst surface, which is a pressing issue during up-conversion of pyrolysis oil and various petrochemical processes.